Clinical implications of age‐related change of the mandibular plane angle. (1st October 2019) - Hardin, Anna M.; Valiathan, Manish; Oh, Heesoo; Knigge, Ryan P.; McNulty, Kieran P.; Leary, Emily V.; Duren, Dana L.; Sherwood, Richard J.
Abstract: Objective: To identify trajectories of ontogenetic change in the mandibular plane angle (MPA) and to describe the influence of sex and other factors on MPA during growth. Setting/Sample: The data consisted of 7026 MPA measurements from lateral cephalographs representing longitudinal series from ages 6 to 21 for 728 individuals from the Craniofacial Growth Consortium Study (CGCS). Materials and Methods: Facial type was determined from MPA for each assessment, with the assessment closest to age 18 representing the adult facial type. The sample includes 366 males and 362 females, each with between 2 and 15 cephalographs. The mean number of cephalographs per individual is 10. Variation in childhood MPA (earliest assessment between 6 and 9 years of age) and adult MPA (closest assessment to age 18 between 15 and 21 years of age), and change in MPA from childhood to adulthood were compared by sex and adult facial type using ANOVA and post hoc t tests. Results: Mandibular plane angle decreased from childhood to adulthood in 92% of males and 81% of females, yet increased in 36% of males and 50% of females with the hyper‐divergent adult facial type. Childhood MPA and overall change in MPA were significantly different by adult facial type. Conclusions: Adult facial type is associated with differences in childhood MPA and change in MPA during growth. There are multiple ontogenetic pathways by which an individual can achieve a normo‐divergent adult facial type, and an individual's childhood MPA does not necessarily correspond to his or her adult facial type.